Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine the order of the functions [tex]\( f \)[/tex], [tex]\( g \)[/tex], and [tex]\( h \)[/tex] based on their average rate of change over the interval [tex]\([0, 3)\)[/tex], we need to perform the following steps:
### Step 1: Calculate the average rate of change for [tex]\( f(x) \)[/tex]
Given the values of [tex]\( f(x) \)[/tex]:
[tex]\[ \begin{array}{|c|c|c|c|c|c|c|} \hline x & -1 & 0 & 1 & 2 & 3 & 4 \\ \hline f(x) & -2 & 1 & 4 & 7 & 10 & 13 \\ \hline \end{array} \][/tex]
We focus on the interval [tex]\([0, 3)\)[/tex]:
- [tex]\( f(0) = 1 \)[/tex]
- [tex]\( f(3) = 10 \)[/tex]
The average rate of change of [tex]\( f \)[/tex] over [tex]\([0,3)\)[/tex] is given by:
[tex]\[ \frac{f(3) - f(0)}{3 - 0} = \frac{10 - 1}{3 - 0} = \frac{9}{3} = 3.0 \][/tex]
### Step 2: Calculate the average rate of change for [tex]\( h(x) \)[/tex]
The function [tex]\( h(x) \)[/tex] is defined as:
[tex]\[ h(x) = x^2 + x - 6 \][/tex]
We evaluate [tex]\( h(x) \)[/tex] at the boundaries of the interval [tex]\([0, 3)\)[/tex]:
- [tex]\( h(0) = 0^2 + 0 - 6 = -6 \)[/tex]
- [tex]\( h(3) = 3^2 + 3 - 6 = 9 + 3 - 6 = 6 \)[/tex]
The average rate of change of [tex]\( h \)[/tex] over [tex]\([0,3)\)[/tex] is given by:
[tex]\[ \frac{h(3) - h(0)}{3 - 0} = \frac{6 - (-6)}{3 - 0} = \frac{6 + 6}{3} = \frac{12}{3} = 4.0 \][/tex]
### Step 3: Calculate the average rate of change for [tex]\( g(x) \)[/tex]
Assume the function [tex]\( g(x) \)[/tex] is defined as:
[tex]\[ g(x) = x^2 + 3x - 4 \][/tex]
We evaluate [tex]\( g(x) \)[/tex] at the boundaries of the interval [tex]\([0, 3)\)[/tex]:
- [tex]\( g(0) = 0^2 + 3(0) - 4 = -4 \)[/tex]
- [tex]\( g(3) = 3^2 + 3(3) - 4 = 9 + 9 - 4 = 14 \)[/tex]
The average rate of change of [tex]\( g \)[/tex] over [tex]\([0,3)\)[/tex] is given by:
[tex]\[ \frac{g(3) - g(0)}{3 - 0} = \frac{14 - (-4)}{3 - 0} = \frac{14 + 4}{3} = \frac{18}{3} = 6.0 \][/tex]
### Step 4: Order the functions by their average rate of change
We have the average rates of change for each function:
- [tex]\( f \)[/tex]: 3.0
- [tex]\( h \)[/tex]: 4.0
- [tex]\( g \)[/tex]: 6.0
Ordering these rates from least to greatest, we get:
1. [tex]\( f \)[/tex] (3.0)
2. [tex]\( h \)[/tex] (4.0)
3. [tex]\( g \)[/tex] (6.0)
Thus, the order of the functions from least to greatest according to their average rate of change over the interval [tex]\([0, 3)\)[/tex] is:
[tex]\[ \boxed{f, h, g} \][/tex]
### Step 1: Calculate the average rate of change for [tex]\( f(x) \)[/tex]
Given the values of [tex]\( f(x) \)[/tex]:
[tex]\[ \begin{array}{|c|c|c|c|c|c|c|} \hline x & -1 & 0 & 1 & 2 & 3 & 4 \\ \hline f(x) & -2 & 1 & 4 & 7 & 10 & 13 \\ \hline \end{array} \][/tex]
We focus on the interval [tex]\([0, 3)\)[/tex]:
- [tex]\( f(0) = 1 \)[/tex]
- [tex]\( f(3) = 10 \)[/tex]
The average rate of change of [tex]\( f \)[/tex] over [tex]\([0,3)\)[/tex] is given by:
[tex]\[ \frac{f(3) - f(0)}{3 - 0} = \frac{10 - 1}{3 - 0} = \frac{9}{3} = 3.0 \][/tex]
### Step 2: Calculate the average rate of change for [tex]\( h(x) \)[/tex]
The function [tex]\( h(x) \)[/tex] is defined as:
[tex]\[ h(x) = x^2 + x - 6 \][/tex]
We evaluate [tex]\( h(x) \)[/tex] at the boundaries of the interval [tex]\([0, 3)\)[/tex]:
- [tex]\( h(0) = 0^2 + 0 - 6 = -6 \)[/tex]
- [tex]\( h(3) = 3^2 + 3 - 6 = 9 + 3 - 6 = 6 \)[/tex]
The average rate of change of [tex]\( h \)[/tex] over [tex]\([0,3)\)[/tex] is given by:
[tex]\[ \frac{h(3) - h(0)}{3 - 0} = \frac{6 - (-6)}{3 - 0} = \frac{6 + 6}{3} = \frac{12}{3} = 4.0 \][/tex]
### Step 3: Calculate the average rate of change for [tex]\( g(x) \)[/tex]
Assume the function [tex]\( g(x) \)[/tex] is defined as:
[tex]\[ g(x) = x^2 + 3x - 4 \][/tex]
We evaluate [tex]\( g(x) \)[/tex] at the boundaries of the interval [tex]\([0, 3)\)[/tex]:
- [tex]\( g(0) = 0^2 + 3(0) - 4 = -4 \)[/tex]
- [tex]\( g(3) = 3^2 + 3(3) - 4 = 9 + 9 - 4 = 14 \)[/tex]
The average rate of change of [tex]\( g \)[/tex] over [tex]\([0,3)\)[/tex] is given by:
[tex]\[ \frac{g(3) - g(0)}{3 - 0} = \frac{14 - (-4)}{3 - 0} = \frac{14 + 4}{3} = \frac{18}{3} = 6.0 \][/tex]
### Step 4: Order the functions by their average rate of change
We have the average rates of change for each function:
- [tex]\( f \)[/tex]: 3.0
- [tex]\( h \)[/tex]: 4.0
- [tex]\( g \)[/tex]: 6.0
Ordering these rates from least to greatest, we get:
1. [tex]\( f \)[/tex] (3.0)
2. [tex]\( h \)[/tex] (4.0)
3. [tex]\( g \)[/tex] (6.0)
Thus, the order of the functions from least to greatest according to their average rate of change over the interval [tex]\([0, 3)\)[/tex] is:
[tex]\[ \boxed{f, h, g} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.